The Subjugation of Bodies, Gender, and Biopolitics in Nawal El Saadawi's Woman at Point Zero - Ali Mohammed Hasan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The subject of patriarchal systems, especially in eastern societies, has attracted literary writers, activists, and politicians, because of its importance and direct effect on women. The present study examines the subjugation of women's bodies, gender roles, and biopolitics in one of Nawal El Saadawi’s novels: Woman at Point Zero (WPZ). For accomplishing the aim of the study, the research has adopted Michel Foucault’s theory of power relations as the theoretical framework. It, through the analysis, examines patriarchal structures in African and Middle Eastern societies and their role in strengthening male dominance and preserving the systemic oppression of women. Firdaus, the novel's protagonist, develops as a strong symbol of female suffering and resistance under a system of psychological, physical, and sexual control. The study discloses how internalized trauma and cultural conditioning lead to the unconscious submission of women. It further explains the impact of religious and cultural bases on deepening female oppression and provides vision on how modern theory, especially Foucauldian biopolitics, can critically engage with these systems of dominance.